Telehealth and occupational therapy in schools (Telehealth and occupational therapy series, 2021)
As telehealth and virtual instruction in schools become commonplace, occupational therapy practitioners have the opportunity to apply their flexibility, adaptability, and unique skill set to serve students in schools, regardless of physical location. This text, the first in a series on telehealth by AOTA, acknowledges that telehealth is a critical part of school-based occupational therapy. It equips practitioners to effectively bridge the digital divide, ensure equitable access to services, determine whether telehealth is an appropriate fit, and work with caregivers for the best possible outcomes. Case examples illustrate how to apply content in realistic scenarios. Practical and evidence based, practitioners can immediately integrate information into their occupational therapy practice to support students and participation in school"--Publisher's description.